Numerical investigation of the effects of hydrogen/ammonia addition to n-heptane combustion and emissions for a dual injection compression-ignition engine - K. Ghadamkheir; F. Safamanesh; M. Moghiman; M. Hatami (Heliyon)
This research employs a detailed chemical mechanism to investigate the spraying of hydrogen and ammonia through dual-channel injector nozzles in a compression ignition engine.This method allows n-heptane, as the diesel primary reference fuel, and hydrogen/ammonia, as carbon-neutral fumigants, to be directly injected into the combustion chamber. The main objective is to predict how substituting a portion of the primary carbon-based fuel with these synthetic fuels affects engine performance and exhaust emissions. Numerical analysis is conducted to evaluate the impact of combustion parameters variation for each simulated fuel condition. One key finding is that optimal combustion timing for both ammonia and hydrogen enables the system to operate normally while achieving substantial emission reductions with no loss in performance. Results indicate that carbon monoxide emissions decrease by 86.7 % with hydrogen injection and 92.5 % with ammonia injection, while CO₂ output is reduced by approximately 18.2 % for both hydrogen and ammonia blends with the primary fuel. The study also investigates the Soot-NOx trade-off, revealing significant insights into emission control strategies. Furthermore, the carcinogenic emissions of hydrogen cyanide and formaldehyde are assessed, showing substantial reductions when utilizing the dual-channel spray system compared to the base engine.